THE INFLUENCE OF PROBLEM SOLVING LEARNING MODELS ON STUDENTS CRITICAL THINKING SKILLS IN INTEGRATED SOCIAL STUDIES SUBJECTS AT JUNIOR HIGH SCHOOL 11 SAMARINDA - Audrey, Audrey Ferina Irawati Rahayu; Sudarman, Sudarman; Sutrisno, Sutrisno (Faculty of Teacher Training and Education, Mulawarman University, 2023)
When learning is carried out at Junior High School 11 Samarinda, it tends to only use the lecture learning model. Based on initial observations carried out by researchers through interviews and obtaining data on student learning outcomes from the Integrated Social Sciences teacher at Junior High School 11 Samarinda. It is known that students do not play an active role in the learning process, which results in a lack of student creativity so that learning outcomes do not reach the criteria for completeness This study aims to determine the effect of the Problem Solving Learning Model on Students' Thinking Ability in Integrated Social Studies Subjects at Junior High School 11 Samarinda. This research is a quantitative research with the type of quasi-experimental research with research subjects in class VIII A as many as 28 students as the control class and VIII B as many as 30 students as the experimental class. Data collection was carried out in this study using observation techniques, tests and interviews. The results of this study were obtained from a simple linear regression test with a sig 2 tailed value <0.05 with a calculation of 0.179 <0.05. So it can be concluded that the use of the problem solving learning model makes students have increased intellectual potential within themselves and students have a sense of self-confidence in expressing their opinions and ideas so that it can stimulate the development of students' thinking abilities creatively and comprehensively, because in the student learning process uses a lot of mental energy to highlight problems from various aspects and approaches in order to find solutions. Keyword: Problem Solving and Critical Thinking Ability When learning is carried out at Junior High School 11 Samarinda, it tends to only use the lecture learning model. Based on initial observations carried out by researchers through interviews and obtaining data on student learning outcomes from the Integrated Social Sciences teacher at Junior High School 11 Samarinda. It is known that students do not play an active role in the learning process, which results in a lack of student creativity so that learning outcomes do not reach the criteria for completeness This study aims to determine the effect of the Problem Solving Learning Model on Students' Thinking Ability in Integrated Social Studies Subjects at Junior High School 11 Samarinda. This research is a quantitative research with the type of quasi-experimental research with research subjects in class VIII A as many as 28 students as the control class and VIII B as many as 30 students as the experimental class. Data collection was carried out in this study using observation techniques, tests and interviews. The results of this study were obtained from a simple linear regression test with a sig 2 tailed value <0.05 with a calculation of 0.179 <0.05. So it can be concluded that the use of the problem solving learning model makes students have increased intellectual potential within themselves and students have a sense of self-confidence in expressing their opinions and ideas so that it can stimulate the development of students' thinking abilities creatively and comprehensively, because in the student learning process uses a lot of mental energy to highlight problems from various aspects and approaches in order to find solutions.